Aplikasi Tandan Kosong Kelapa Sawit dan Limbah Cair Pabrik Kelapa Sawit pada Tanaman Kelapa Sawit Menghasilkan (Elaeis Guineensis Jacq): Application of Palm Oil Empty Fruit Bunches and Palm Oil Mill Effluent in Producing Palm Oil Plants (Elaeis guineensis Jacq.) - Priambodo, Okta Nindita; Erdiansyah, Naufal Al-Fattah (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2024)
Oil palm is one of the important plantation commodities in Indonesia, with a plantation area reaching 14.33 million hectares and continuing to grow. This growth has led to an increase in the number of oil palm processing factories, which produce solid waste of Empty Fruit Bunches (EFB) and liquid waste of Palm Oil Mill Effluent (POME). If not processed properly, this waste can pollute the environment. However, this waste can be used as organic fertilizer that is rich in nutrients, reducing dependence on inorganic fertilizers, and saving costs. At the Rama-Rama Oil Palm Plantation, this waste is used as a soil conditioner and source of nutrients, with the hope of increasing oil palm productivity. This study aims to determine the effect of EFB and POME applications on oil palm productivity by comparing productivity between land applied with EFB and POME using the Independent T Test method at a real level of 5%. The results of observations show that POME and EFB applications affect the production of fresh oil palm fruit bunches, the number of fresh oil palm bunches, and the weight of oil palm bunches. POME application has a greater impact on the production of fresh oil palm fruit bunches, the number of fresh oil palm bunches, and the weight of oil palm bunches compared to EFB application and without POME and EFB application. The average production of fruit bunches in the EFB and POME blocks each month is above its production potential according to the land suitability level of class S2.